The Empirical Factors Determining Vertical Integration in Algerian Food Manufacturing Sector - Benmehaia, Amine M.; Brabez, Fatima (European Scientific Journal, ESJ, 2016)
This paper examines the empirical factors determining vertical integration in the food manufacturing industry in Algeria. In this research, we focus on the effects of food industry structure, transaction costs, and several market conditions. We use data for the period of 16 years (2000- 2015) to estimate a linear regression model. Through an econometric analysis, three vertical integration measures are utilized to examine the determinants of vertical integration in food manufacturing industry. Empirical results support that there are variations in terms of the effects of industry structure and market conditions, whereas the transaction costs involved in the food industry coordination seems to have a significant effect on vertical integration trends.